2015
DOI: 10.1136/bmjspcare-2014-000748
|View full text |Cite
|
Sign up to set email alerts
|

A survey of patients’ experience of pain and other symptoms while receiving care from palliative care services

Abstract: Context In Australia, patients at the end of life with complex symptoms and needs are often referred to palliative care services (PCSs), but little is known about the symptoms of patients receiving palliative care in different settings.Objective To explore patients' levels of pain and other symptoms while receiving care from PCSs.Method PCSs registered through Australia's national Palliative Care Outcomes Collaboration (PCOC) were invited to participate in a survey between 2008 and 2011. Patients (or if unable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 17 publications
3
32
0
5
Order By: Relevance
“…A consumer survey involving 13 different Australian palliative care services confirms this observation, with 35% of patients reporting having moderate-severe pain which restricted their activity over the preceding three days (Palliative Care Outcomes Collaboration, 2012). Similar results have been reported in the most recent consumer survey (Pidgeon et al, 2015). So even within specialties, where pain management is a core competency, there are opportunities to improve the pain outcomes for patients by strengthening nurses' routine screening and pain assessment capabilities.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…A consumer survey involving 13 different Australian palliative care services confirms this observation, with 35% of patients reporting having moderate-severe pain which restricted their activity over the preceding three days (Palliative Care Outcomes Collaboration, 2012). Similar results have been reported in the most recent consumer survey (Pidgeon et al, 2015). So even within specialties, where pain management is a core competency, there are opportunities to improve the pain outcomes for patients by strengthening nurses' routine screening and pain assessment capabilities.…”
Section: Introductionsupporting
confidence: 83%
“…Internationally, evidence of screening and assessment practices are increasingly being recognized as quality indicators of optimal cancer pain management (Dy et al, 2008). In Australia, specialist palliative care services are routinely required to capture the daily average pain intensity scores of inpatients and during every home visit for community patients, while there is no such obligation for cancer services (Pidgeon et al, 2015). However, a study conducted within one large Australian specialist palliative care service found little documented evidence of either routine pain screening and/or comprehensive pain assessments being routinely undertaken when pain was identified (Phillips & Piza, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Unrelieved pain is a major issue in specialist palliative care,15 and it appears opioid errors, particularly omitted dose errors, may be contributing to the burden of palliative patients’ pain. Better understanding the factors that contribute to or mitigate opioid errors, including systems factors and the impact of error reporting culture, and developing strategies to prevent iatrogenic pain occurring as a result of opioid errors, is a priority for this clinical setting and population.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and families may underreport even severe and distressing symptoms, 4 and when asked to evaluate symptom control away from the clinical review, patients and their caregivers paint a picture of poorly controlled symptoms as a source of significant distress. 5…”
mentioning
confidence: 99%